Optimizing Retail Strategy with IBM Retail Data Warehouse (RDW): A Short Review of Data-Driven Approach to Customer-Centric Decision-Making - Santos Fernandez, Maria (Jejaring Penelitian dan Pengabdian Masyarakat, 2025)
Retail businesses operate in highly competitive and unpredictable environments where customer demands continue to evolve rapidly. Whether catering to niche markets with premium products or competing at scale as mega retailers, businesses must deeply understand their customers and develop strategies that align with their preferences, behaviors, and expectations. Simply recording raw data is insufficient to gain meaningful insights; retail businesses must leverage advanced business intelligence tools to visualize and analyze data effectively. The integration of data mining techniques with business analytics plays a crucial role in extracting actionable intelligence, enabling retailers to enhance customer experiences, optimize inventory management, and improve operational efficiency. This paper explores the IBM Retail Data Warehouse (RDW) as a comprehensive solution for data-driven decision-making in the retail sector. By implementing robust data integration and governance frameworks, businesses can enhance their ability to derive valuable insights, streamline operations, and maintain a competitive edge in the dynamic retail landscape. Ultimately, mastering data-driven strategies through IBM RDW empowers retail businesses to transition from reactive decision-making to proactive, customer-centric approaches, ensuring long-term growth and sustainability in an ever-changing market.